Optimization of Polyurethane Membrane Physical Characteristics of Red Seaweed Biomass Using a Box-Behnken Design - Salfauqi Nurman; Saiful Saiful; Binawati Ginting; Rahmi Rahmi; Marlina Marlina (Indonesian Journal of Chemistry, 2021)
The polyurethane membrane is used as a separator either by filtration or adsorption, and this process is significantly affected by its strength and physical condition. We synthesized polyurethane membranes using red seaweed with Gracilaria sp as a hydroxyl source. The Box-Behnken Design of the Response Surface Methodology (RSM) using Software Design Expert Version 10.0.3.0 with three factors (TRL, TDI, and Glycerin). The F-value of 0.42 suggests that the membrane is less fit, while the P-value of 75.10% indicates that the quadratic design model is suitable for data analysis of physical characteristics. The optimal physical characteristics were obtained at a composition of 0.233 g TRL, 2.675 g TDI, and 0.254 g glycerin with a physical point of 6.5 (strong and elastic). Optimal polyurethane membrane has good thermal and mechanical properties at temperatures of Tg 58 °C, Tm 322 °C, and Td 534 °C, as well as stress and nominal strain values of 69.3 MPa and 5.74%. Polyurethane membrane synthesized from red seaweed has good physical properties. The result of this research is the basis for the development of polyurethane membrane applications from red seaweed.